Gender Equality in Islamic Religious Education - Abdul Karim; Pryla Rochmahwati (IAIN Ponorogo, 2021)
Abstract: This research is remarkable to conduct research dealing with its impact on the senior high school students’ achievement. The design of the research was a phenomenological qualitative approach. It was applied by using purposive sampling in Kudus Regency. The findings showed that (1) Islamic Religious Education placed men and women equally in the teaching and learning process. However, the difference in learning material is based on the essence of the source of Islamic law of Al-Quran and Hadith; (2) There are several learning models applied, directed free learning strategies which stimulate students for behaving and acting according to normative-rational and religious considerations and resulting in learning changes in thinking, behaving and acting according to individual ratio considerations; (3) The impact of the Islamic Religious Education learning model on understanding gender equality is that the presence of a normative-religious, normative-rational understanding, as well as a rational understanding of gender issues. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kesetaraan gender terhadap prestasi belajar peserta didik di Sekolah Menengah Atas (SMA). Penelitian ini mengambil lokasi di Kabupaten Kudus (berdasarkan purposive sampling) dengan menggunakan pendekatan kualitatif fenomenologis. Dari hasil analisis data penelitian ditemukan, pertama: Pembelajaran PAI dilaksanakan dengan tanpa membedakan gender peserta didik. Perbedaan materi pembelajaran didasarkan pada esensi sumber hukum Islam al-Quran dan Hadits. Kedua, terdapat beberapa model pembelajaran yang diterapkan, yaitu dengan menggunakan strategi pembelajaran bebas terarah yang merangsang siswa untuk berperilaku dan bertindak sesuai pertimbangan normatif-rasional dan religius sehingga mengakibatkan perubahan sikap peserta didik dalam berpikir, berperilaku dan bertindak sesuai dengan pertimbangan rasio individu. Ketiga, ada beberapa dampak model pembelajaran PAI terhadap pemahaman kesetaraan gender, di antaranya: model pertama, peserta didik memiliki pemahaman secara normatif-religius; model kedua, peserta didik memiliki pemahaman tentang gender secara normatif-rasional; dan model pembelajaran ketiga, peserta didik memiliki pemahaman permasalahan gender secara rasional.